Screening Internal Contamination of Inhaled and Ingested Radionuclides with Hand-held Survey Meters. Issue 3 (March 2018) - Adams, Tim G.; Casagrande, Rocco
Abstract : Abstract: During the aftermath of a radiological accident or attack, the rapid identification of individuals who have internalized medically significant amounts of material is paramount to guide medical and public health decisions. This paper explores the utility of hand-held, pancake GM detectors to determine if an individual has inhaled 90 Sr, 137 Cs, 238 Pu, 239 Pu, or 241 Am in quantities requiring treatment. Additionally, ingestion of 90 Sr or 137 Cs was considered. Both 90 Sr and 137 Cs were modeled in equilibrium with their progeny, but the progeny of 238 Pu, 239 Pu, and 241 Am were excluded. Treatment thresholds are defined using the National Council on Radiation Protection & Measurements' (NCRP) clinical decision guides (CDGs). Using Monte Carlo N-Particle (MCNP) modeling software, a human phantom and detector were modeled to determine the activity required to achieve a detector reading of twice background 1, 7, or 30 d post-ingestion or post-inhalation. Modeling found that inhaled 238 Pu, 239 Pu, and 241 Am are detectable only if the contaminated individual inhaled thousands-fold more material than the CDG. This lack of detectability means that hand-held GM detectors are inappropriate for initial screening for americium or plutonium and that more intensive screening is necessary to confirm suspected contamination. Cesium-137, by contrast, could be detected at levels 10‐ to 100‐fold lower than the amount requiring treatment, allowing quick differentiation between contaminated and uncontaminated individuals. Surprisingly, 90 Sr was detectable within a factor of 2 of the amount requiring treatment. Detection of 90 Sr was due primarily to bremsstrahlung radiation from beta interactions with calcium in bone. While rapid screening could identify individuals contaminated by 137 Cs and possibly with 90 Sr, further screening of identified individuals is necessary to establish medical need. However, these contaminated individuals could still be prioritized for further testing and possible presumptive treatment. Based on the findings of this study, concepts of operation for the use of hand-held survey meters should be developed for the screening of individuals potentially internally contaminated with 137 Cs and 90 Sr.